PENGARUH PERIKLANAN DAN ATRIBUT PRODUK DALAM MENINGKATKAN BRAND AWARENESS PADA ONLINE SHOP DENIM DELUGE COMPANY - Sutarso, Muhammad Fadhol Arofah; Handrito , Radityo Putro (Fakultas Ekonomi dan Bisnis Universitas Brawijaya, 2022)
Advertising and product attributes are useful for every company that wants to market its products and instill in consumers' minds that the company sells a product with unique product attributes, consumers unconsciously instill in their minds that a product is in the first thought when consumers are looking for a product. specific product category. This study aims to determine the effect of advertising and product attributes on brand awareness of Deluge Company's Instagram followers. The type of research used is quantitative with inferential descriptive analysis techniques. The method of data collection carried out in this study used a questionnaire measured by a Likert scale with a total of 160 respondents. Data analysis was carried out using multiple linear regression models to determine the effect of each variable on increasing brand awareness. The results of this study indicate that advertising variables and product attributes have a positive influence on increasing brand awareness. Based on this research, the implications that can be given are developing and introducing more detailed product attributes so as to increase awareness in the minds of consumers. And another implication is maximizing the ads on Deluge Company's social.